2011
DOI: 10.1186/1476-511x-10-225
|View full text |Cite
|
Sign up to set email alerts
|

Endurance exercise is a leptin signaling mimetic in hypothalamus of Wistar rats

Abstract: BackgroundEndurance exercise is known to promote a substantial effect on the energy balance in rats and humans. However, little is known about the exact mechanisms for the appetite-suppressive effects of endurance exercise. We hypothesized that endurance training might activate signaling cascades in the hypothalamus known to be involved in leptin signaling.Methods16 male Wistar rats were randomly assigned to two groups: sedentary (n = 8) and exercise groups (n = 8). Animals in the exercise group started treadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 56 publications
(56 reference statements)
2
20
1
2
Order By: Relevance
“…Changes in leptin and insulin levels contribute to the complex regulation of food intake (23,24) and exercise is known to reduce leptin and insulin contributing to the modulation of energy homeostasis (15,25). Recent work has led to the proposal that physical activity favours the peripheral action of leptin through an increased central sensitivity (15) and this may promote a thermogenic effect, explaining the reduction that we observed in WAT depots.…”
Section: Discussionmentioning
confidence: 71%
“…Changes in leptin and insulin levels contribute to the complex regulation of food intake (23,24) and exercise is known to reduce leptin and insulin contributing to the modulation of energy homeostasis (15,25). Recent work has led to the proposal that physical activity favours the peripheral action of leptin through an increased central sensitivity (15) and this may promote a thermogenic effect, explaining the reduction that we observed in WAT depots.…”
Section: Discussionmentioning
confidence: 71%
“…Interestingly, we previously found that deletion of Foxo1 in the VMH increases SF-1 mRNA levels in the hypothalamus (Kim et al, 2012), suggesting that PI3K signaling regulates SF-1 expression levels in the VMH in vivo. While studies suggest that exercise can activate PI3K signaling in the hypothalamus after exercise training (Chiarreotto-Ropelle et al, 2013; Zhao et al, 2011), it remains unclear whether this occurs specifically in SF-1 neurons. Exercise training also increases several neurotrophic factors in the hippocampus, including BDNF, which activate the PI3K signaling pathway (Cotman et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The treadmill was equipped with an electric-shock grid on the rear barrier to provide exercise motivation. Animals in the E group began treadmill running at 30 m/min with a 0% grade for 1 min/bout in accordance with our previous study of endurance training animal models [35]. Running time was gradually increased by 2 min/bout every day during the 1st-5th weeks and the 8th-11th weeks and to 2 bouts/day during the 3rd-11th weeks to reach 254 min/day for the final week.…”
Section: Animals Protocols and Samplingmentioning
confidence: 88%